CREATIVE ACCOUNTING AND THE GODFATHER STUDI KASUS PADA PT. GBU - Luky Amelia Chandra (Perpustakaan Universitas Surabaya, 2017)
Abstract Purpose - This study aims to improve understanding of the creative accounting, so that it can detect the presence of creative accounting and how big the role of